Teacher Performance at State Middle School - Hidayat, Muhammad Nur; Pawenang, Supawi; DWP, Ida Aryati (Journal of Education Research, 2024)
Teacher performance reviewed from work motivation, organizational commitment, leadership style, and organizational culture at SMP Negeri 1 Ngawen Blora. This study aims to determine and explain the effect of work motivation, organizational commitment, leadership style, and organizational culture on teacher performance at SMP Negeri 1 Ngawen Blora. The population of this study was all teachers at SMP Negeri 1 Ngawen Blora totaling 46 people with a saturated sample technique. Data collection using a questionnaire. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that work motivation, organizational commitment, leadership style, and organizational culture influenced teacher performance at SMP Negeri 1 Ngawen Blora by 72.1% while the remaining 27.9% was explained by other variables not proposed in this study. Suggestions from this study, teachers at SMP Negeri 1 Ngawen Blora can improve work motivation, organizational commitment, and good organizational culture through a leadership style that is suitable to achieve maximum performance results for SMP Negeri 1 Ngawen Blora.